1994
DOI: 10.1128/mcb.14.11.7322
|View full text |Cite
|
Sign up to set email alerts
|

Cap-dependent and cap-independent translation by internal initiation of mRNAs in cell extracts prepared from Saccharomyces cerevisiae.

Abstract: Translation extracts were prepared from various strains of Saccharomyces cerevisiae. The translation of mRNA molecules in these extracts was cooperatively enhanced by the presence of 5'-terminal cap structures and 3'-terminal poly(A) sequences. These cooperative effects could not be observed in other translation systems such as those prepared from rabbit reticulocytes, wheat germ, and human HeLa cells. Because the yeast translation system mimicked the effects of the cap structure and poly(A) tail on translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
230
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(242 citation statements)
references
References 49 publications
11
230
1
Order By: Relevance
“…Later, a strong synergism between the cap structure and the poly(A) tail during translation initiation was discovered, first in electroporated cells (68) and subsequently in cell-free translation systems of different origins. (69)(70)(71)(72) In a yeast cell-free system, the poly(A) tail, like the cap structure, was able to support the recruitment of the 40S ribosomal subunit by itself to an uncapped mRNA. (73) This function of the poly(A) tail as well as the functional synergy with the cap structure requires the poly(A)-binding protein (PABP) (73) and its interaction with the N-terminal part of eIF4G (74,75) (Fig.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…Later, a strong synergism between the cap structure and the poly(A) tail during translation initiation was discovered, first in electroporated cells (68) and subsequently in cell-free translation systems of different origins. (69)(70)(71)(72) In a yeast cell-free system, the poly(A) tail, like the cap structure, was able to support the recruitment of the 40S ribosomal subunit by itself to an uncapped mRNA. (73) This function of the poly(A) tail as well as the functional synergy with the cap structure requires the poly(A)-binding protein (PABP) (73) and its interaction with the N-terminal part of eIF4G (74,75) (Fig.…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%
“…The Renilla luciferase version of these, i.e., p-Bluescript-BREF and p-Bluescript-BmR(EF)m, were generated by exchanging the firefly luciferase (Fluc) ORF by the Renilla version derived from the pRL-null plasmid (Promega), using XmaI and HpaI restriction sites. The plasmids bearing the Fluc ORF or chloramphenicol acetyl transferase (CAT) under the transcriptional control of T3 and T7 polymerases were previously described (Iizuka et al 1994;Gebauer et al 1999). Rluc, Fluc, and CAT reporter mRNAs were transcribed using the linearized (HindIII) plasmids in the presence of m7GpppG cap (KEDAR S.C.) using T7 or T3 in vitro transcription kits (MEGAscript; Thermo Fisher Scientific) following the manufacturer's recommendations.…”
Section: Plasmids and In Vitro Transcriptionmentioning
confidence: 99%
“…These results suggest that cells can survive by using a cap-independent mechanism of initiating translation. Other studies have identified IRESes within the yeast TFIID and HAP4 mRNAs, which were shown to function in yeast cell-free lysates (21), and in the YAP1 and p150 mRNAs, which we showed can function in vegetatively growing cells (22). The ability of yeast cells to initiate translation internally is also supported by the observations that RNA sequences from various organisms and sources, including the cricket paralysis virus, can function as IRESes in yeast (23)(24)(25).…”
mentioning
confidence: 99%